Home bias in foreign investment decisions - Ke, Dongmin; Ng, Lilian; Wang, Qinghai (Journal of International Business Studies, 2010)
We analyze the US equity holdings of more than 3000 non-US-based mutual funds from 22 countries and find robust evidence that fund managers strongly prefer to invest in stocks of US firms that have presence in their home country. This “home bias” is independent of the degree of global involvement and visibility of these US firms. While these firms have significantly greater exposure to local equity markets, their local presence offers little information advantage to local fund managers. Our findings suggest that the lack of international diversification is more serious than currently documented in the literature.